Systematic Literature Review on the Implementation of Unmanned Ground Vehicle System (UGVS) for Defense in Indonesia - La Ode Murgazali Bakasa; S Martha; S. Arief; Muhammad Ihsan (CV. AFDIFAL MAJU BERKAH, 2024)
This research conducts a systematic literature review to examine the implementation of Unmanned Ground Vehicle System (UGVS) in the context of defense in Indonesia. Given the geographical and operational challenges faced by Indonesian military personnel, UGVS offers an innovative solution to improve the efficiency and effectiveness of military and non-military operations. This study considers the application of UGVS that has been adopted in several developed countries, such as the United States, the United Kingdom, Israel, China and Russia, to explore its potential in enhancing Indonesia's defense capacity. The review covers aspects such as the potential of UGVS in enhancing defense capabilities, technical challenges in the integration of UGVS into existing defense systems, and strategies to overcome these challenges. The research also evaluates the performance of UGVS in combat situations and its impact on defense operations. Using a systematic literature review method, this research presents an in-depth analysis of UGVS applications and highlights the need for integration of this technology in Indonesia's defense system to improve operational effectiveness and efficiency.